2020
DOI: 10.1001/jamaoncol.2020.3152
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Laparoscopic vs Open Total Gastrectomy for Clinical Stage I Gastric Cancer

Abstract: IMPORTANCEThe safety of laparoscopic total gastrectomy (LTG) for the treatment of gastric cancer remains uncertain given the lack of high-level clinical evidence.OBJECTIVE To compare the safety of LTG for clinical stage I gastric cancer with that of conventional open total gastrectomy (OTG). DESIGN, SETTING, AND PARTICIPANTSThe Chinese Laparoscopic Gastrointestinal Surgery Study (CLASS) Group CLASS02 study was a prospective, multicenter, open-label, noninferiority, randomized clinical trial that compared the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 35 publications
3
111
1
5
Order By: Relevance
“…It was reported by the Korean Laparoendoscopic Gastrointestinal Surgery Study (KLASS) group that laparoscopic gastrectomy was related with much better short-term outcomes such as less blood loss, less severe postoperative pain, faster recovery, and much shorter hospital stay and similar long-term oncological outcomes [ 7 ]. In a multicenter randomized clinical trial published in 2020, similar conclusions were drawn [ 5 ]. Thus, as far as we are concerned, in most guidelines and multicenter clinical trial, laparoscopic gastrectomy is recommended as the treatment of choice for early-stage GC.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…It was reported by the Korean Laparoendoscopic Gastrointestinal Surgery Study (KLASS) group that laparoscopic gastrectomy was related with much better short-term outcomes such as less blood loss, less severe postoperative pain, faster recovery, and much shorter hospital stay and similar long-term oncological outcomes [ 7 ]. In a multicenter randomized clinical trial published in 2020, similar conclusions were drawn [ 5 ]. Thus, as far as we are concerned, in most guidelines and multicenter clinical trial, laparoscopic gastrectomy is recommended as the treatment of choice for early-stage GC.…”
Section: Introductionsupporting
confidence: 56%
“…Oncological safety of laparoscopic gastrectomy plus D2 lymphadenectomy for locally advanced gastric cancer (most were stages II and III) has previously been proven by a few large randomized clinical trials [ 9 , 12 , 20 ]. In these studies and other reports, it was reported that in comparison with open surgery, laparoscopic gastrectomy plus D2 lymphadenectomy was related with significantly lower intraoperative and postoperative complication rates and quicker recovery [ 5 , 7 , 9 , 12 , 20 ]. However, for stage I GC, a D2 lymphadenectomy is not always indicated and concerns about risks and benefits of laparoscopic gastrectomy plus D2 lymphadenectomy have not been fully resolved [ 5 , 7 , 21 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Radical resection of gastric cancer lesions combined with adequate lymph node dissection is key to treatment of gastric cancer. However, radical resection of gastric cancer is still technically di cult the incidence of postoperative complications (POCs) of gastric cancer was reported to be 12.9 24.4% [3][4][5].The most common POCs are anastomotic problems, obstruction, infectious complications such as pneumonia, abdominal abscess, urinary tract infection, incision infection, etc.…”
Section: Introductionmentioning
confidence: 99%
“…East Asia, including China, has a high incidence of gastric cancer 1,2 . Although much progress has been made in improving the quality of life of gastric cancer patients [3][4][5] , the overall survival of GC patients has remained unsatisfactory in recent years 6 . Therefore, it is valuable to explore the potential mechanism and identify possible clinical therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%